The Effectiveness of Learning to Read and Write Arabic Letters in Early Children at Taman Pendidikan Quran (TPQ) - Nuril Mufidah; Rifka Arifatul Choridah; Inaad Mutlib Sayer (Bulletin of Early Childhood, 2022)
The purpose of this study is to describe process of learning to read and write Arabic letters in early childhood at Taman Pendidikan Quran (TPQ) Nurul Muttaqin 4, the students' interest in learning, positive impacts or benefits for students, opportunities in learning, and challenges faced during learning. The research method used is qualitative with the subject of early childhood aged 4-8 years at TPQ Nurul Muttaqin 4. Data collection techniques by observing the teaching and learning process of students and interviews with one of the teachers and students concerned. The research results obtained include: 1. The process of learning to read and write Arabic letters for early childhood at TPQ Nurul Muttaqin 4 using the iqro' method for reading and writing 2. The students' interest in learning is very large in learning because the parents of the students support it. and very open so that students are very interested in this learning. 3. The positive impact or benefits obtained by the students vary after participating in learning using the iqro' method, because each child has a different level of ability. There are children who are proficient in reading but lacking in writing Arabic letters. Vice versa. 4. The opportunities for learning are very good because the surrounding community is supportive and open with evidence that their children are entrusted to study at this TPQ. 5. The challenge faced during learning is the feeling of drowsiness that comes to students during learning, which makes it difficult for students to concentrate. The solution that can be done is that teachers can make learning as interesting as possible so that it makes students enthusiastic and interested in learning.